সুবা বাংলার ভূ-অভিজাততন্ত্র - রহমান, মোঃ হাবিবুর, ১৯৬৪- (ঢাকা : বাংলা একাডেমী, 2003)
History of feudalism in Bengal, India between 1717 and 1765.
গ্রন্থপঞ্জিগত নির্দেশিকা অন্তর্ভুক্ত (পৃষ্ঠা ২২২-২৩০).
BIED
Complimentary copy from BIED
In Bengali.
Keywords: Feudalism -- India -- History; Feudalism -- India -- Bengal -- History -- 18th century; Bengal (India) -- Social conditions -- 18th century; Bengal (India) -- Politics and government -- 18th century